Selecting optimal drug-intervention in a pathway involving receptor tyrosine kinases (RTKs). (May 2016) - Benson, Neil; van der Graaf, Piet H.; Peletier, Lambertus A.
Abstract: A recently developed system-pharmacological model for the dynamics of receptor tyrosine kinases is used to compare different targets for drug action: one aiming at binding endogenous ligand needed for phosphorylation and another binding receptors at their kinase domains and thus preventing them to generate phosphorylation. We obtain quantitative estimates for the effectivity of the inhibitor which demonstrate the influence of drug-properties such as dose, affinity to target and drug-elimination rates. Highlights: A system-pharmacological model has been developed for studying qualitatively and quantitatively cross-membrane signalling via RTK's. It has been shown that the physiological structure, which differentiates between the interstitial fluid and the cellular space, is critical in determining the efficacy of drugs. The efficacy of two different inhibitors, one targeting the top of the pathway (the ligand) and one targeting the bottom of the pathway (the receptor-kinase), has been compared quantitatively.